Synchronous and Asynchronous Boundary Temperature Modulations on Triple-Diffusive Convection in Couple Stress Liquid Using Ginzburg-Landau Model - Sameena, T.; Pranesh, S. (International Journal of Engineering and Technology, 2018)
A nonlinear study of synchronous and asynchronous boundary temperature modulations on the onset of triple-diffusive convection in couple stress liquid is examined. Two cases of temperature modulations are studied: (a) Synchronous temperature modulation ( ) and (b) Asynchronous temperature modulation ( ). It is done to examine the influence of mass and heat transfer by deriving Ginzburg-Landau equation. The resultant Ginzburg-Landau equation is Bernoulli equation and it is solved numerically by means of Mathematica. The influence of solute Rayleigh numbers and couple stress parameter is studied. It is observed that couple stress parameter increases the mass and heat transfer whereas solute Rayleigh numbers decreases the mass and heat transfer.Â